Study of the structure-activity relationship of flavonoids based on their interaction with human serum albumin1. Issue 89 (27th September 2015) - Tu, Bao; Chen, Zhi-Feng; Liu, Zhi-Juan; Li, Rong-Rong; Ouyang, Yu; Hu, Yan-Jun
<x xml:space="preserve">Abstract</x> The influence of functional groups on the interaction has been studied detailed here; fluorescence quenching degrees and the conformation change are considered through multiple methods; molecular docking has been introduced to verify related results.